DASYPOGALACTONE, A NEW CHIRALIC C3-SYMMETRIC MACROLACTONE FROM LICHEN USNEA DASYPOGA ROHL. - Ratna Layla Gani; Wahyudi Priyono Suwarso; Karsten Krohn; Markus John (Indonesian Journal of Pharmacy, 2001)
Medicinal plants spread out in Indonesia, however only a part of them have been clinically investigated that exhibited therapeutic effecs. This research was to isolate a new compounds in Usnea dasypoga. A new twentyfour-membered macrolactone composed of three units of unknown fatty acid (2R*,3R*,4S*,7S* or 2S* 3S* 4R*, 7R*)-3,7-dihydroxy-2,4-dimethyloctanoic acid forming a C3-symmetrical lactide was isolated from Indonesian lichen Usnea dasypoga Rohl. The result shown that those compound had been confirmed with the spectroscopic data.Keywords: Natural products isolation, three lactide, lichen